PENGARUH MODEL PEMBELAJARAN TALKING STICK BERBANTU MEDIA POSTER TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI KEUNIKAN KEBIASAAN MASYARAKAT DI SEKITARKU KELAS IV - Iffatun Nisa', Khikma; Erik Aditia Ismaya; Wawan Shokib Rondli (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research was motivated by the low ability of students to answer questions with high level reasoning abilities in class IV students at SD N 1 Gambiran. Learning that is less interactive causes students' low critical thinking abilities. This is due to the lack of teacher strategies in achieving learning goals. The aim of this research is to determine the effect of the talking stick learning model assisted by poster media on students' critical thinking abilities. This research uses a one group pretest posttest design experimental research type. The population in this study was all fourth grade students at SD N 1 Gambiran, while the sample used was a saturated sample using all fourth grade students. In this research, data collection used observation, interviews, tests and documentation techniques. The data analysis used is the normality test and the paired sample t-test. The results of the paired sample t-test show that the Sig. (2-tailed) is 0.000 < 0.05, then Ho is rejected and Ha is accepted. So it can be concluded that there is an influence of the talking stick learning model assisted by poster media on students' critical thinking abilities.